THE STUDY OF THE SPECIALIZATION SORTING RUTS INFLUENCE ON THE DURATION OF OPERATIONS ON THEIR PREPARATION FOR THE DETACHING - Kozachenko, D. M.; Vernyhora, R. V.; Berezovyi, M. I. (Science and Transport Progress, 2008)
For modeling of the trains accumulation process on marshalling tracks the special simulation model is designed. The model is used for study of the influence of specialization of marshalling tracks on duration of the operations for liquidation of «windows» between cars on marshalling tracks.